The impact of 3-sulfo-taurolithocholic acid on ATPase activity in patients’ colorectal cancer and normal colon tissues, and its hepatic effects in rodents - Bychkova, Solomiia; Bychkov, Mykola; Dordević, Dani; Rittmann, Simon K.-M. R.; Vítězová, Monika; Kushkevych, Ivan (Frontiers in Veterinary Science, 2024)
Colorectal cancer is influenced by genetic mutations, lifestyle factors, and diet, particularly high fat intake, which raises bile acid levels in the intestinal lumen. This study hypothesized that bile acids contribute to tumorigenesis by disrupting ion transport and ATPase activity in the intestinal mucosa. The effects of 3-sulfo-taurolithocholic acid (TLC–S) on ATPase activity were investigated in colorectal cancer samples from 10 patients, using adjacent healthy tissue as controls, and in rodent liver function. ATPase activity was measured spectrophotometrically by determining inorganic phosphorus (Pi) in postmitochondrial fractions. Ca2+ dynamics were assessed in isolated mouse hepatocytes with fluorescence imaging, and rat liver mitochondria were studied using polarographic methods to evaluate respiration and oxidative phosphorylation. TLC–S increased Na+/K+ ATPase activity by 1.5 times in colorectal cancer samples compared to controls (p ≤ 0.05). In healthy mucosa, TLC–S decreased Mg2+ ATPase activity by 3.6 times (p ≤ 0.05), while Mg2+ ATPase activity in cancer tissue remained unchanged. TLC–S had no significant effect on Ca2+ ATPase activity in healthy colon mucosa but showed a trend toward decreased activity in cancer tissue. In rat liver, TLC–S decreased Ca2+ ATPase and Na+/K+ ATPase activities while increasing basal Mg2+ ATPase activity (p ≤ 0.05). Additionally, TLC–S induced cytosolic Ca2+ signals in mouse hepatocytes, partially attenuated by NED-19, an NAADP antagonist (p ≤ 0.05). TLC–S also reduced the V3 respiration rate of isolated rat liver mitochondria during α-ketoglutarate oxidation. These findings suggest that TLC–S modulates ATPase activity differently in cancerous and healthy colon tissues, playing a role in colorectal cancer development. In rat liver, TLC–S affects mitochondrial activity and ATPase function, contributing to altered cytosolic calcium levels, providing insight into the mechanistic effects of bile acids on colorectal cancer and liver function.